Designing an Android-Based Teacher Attendance System to Improve The Quality of Learning in Vocational High Schools - Ashari, Mochammad Ibrahim; Rudhistiar, Deddy; Agustini, Ni Putu; Myrtanti, Reiny Ditta; Sujianto, (TAAWUN, 2025)
This service aims to overcome problems in attendance management at SMK PGRI Sumber Pucung, which is currently still using a manual system, so it can potentially cause recording errors, time inefficiencies, and the risk of data loss during the archiving process. Therefore, as a solution to the existing problem, an Android-based attendance system was developed, where the method applied is the waterfall method, with the implementation carried out in stages starting from problem identification to system evaluation. The results of the service show that the system has succeeded in increasing the efficiency of daily attendance recording time by 66.67% and increasing the recording accuracy by up to 80%, so that this android-based attendance system can overcome problems in manual attendance management at SMK PGRI Sumber Pucung, and can be implemented as a solution to help the school administration process. Attendance system testing shows effective performance and runs well across various platforms. In the admin dashboard test, the test on the student attendance application from 3 test scenarios was successfully carried out as expected, then the test on the student attendance application consisting of 6 scenarios was also successfully carried out according to expectations. Functional testing on the web browser, admin dashboard, and functional testing on the teacher attendance application which has the same scenario, totaling 14, was successfully carried out according to expectations. Testing on the student attendance application that has 4 scenarios was successfully carried out according to expectations.